Atrial fibrillation activates AMP-dependent protein kinase and its regulation of cellular calcium handling: potential role in metabolic adaptation and prevention of progression - Harada, Masahide; Tadevosyan, Artavazd; Qi, Xiaoyan; Xiao, Jiening; Liu, Tao; Voigt, Niels; Karck, Matthias; Kamler, Markus; Kodama, Itsuo; Murohara, Toyoaki; Dobrev, Dobromir; Nattel, Stanley (Journal of the American College of Cardiology, 2015)
Background - Atrial fibrillation (AF) is associated with metabolic stress, which activates adenosine monophosphate-regulated protein kinase (AMPK). - Objectives - This study sought to examine AMPK response to AF and associated metabolic stress, along with consequences for atrial cardiomyocyte Ca2+ handling. - Methods - Calcium ion (Ca2+) transients (CaTs) and cell shortening (CS) were measured in dog and human atrial cardiomyocytes. AMPK phosphorylation and AMPK association with Ca2+-handling proteins were evaluated by immunoblotting and immunoprecipitation. - Results - CaT amplitude and CS decreased at 4-min glycolysis inhibition (GI) but returned to baseline at 8 min, suggesting cellular adaptation to metabolic stress, potentially due to AMPK activation. GI increased AMPK-activating phosphorylation, and an AMPK inhibitor, compound C (CompC), abolished the adaptation of CaT and CS to GI. The AMPK activator 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) increased CaT amplitude and CS, restoring CompC-induced CaT and CS decreases. CompC decreased L-type calcium channel current (ICa,L), along with ICa,L-triggered CaT amplitude and sarcoplasmic reticulum (SR) Ca2+ content under voltage clamp conditions in dog cells and suppressed CaT and ICa,L in human cardiomyocytes. Small interfering ribonucleic acid-based AMPK knockdown decreased CaT amplitude in neonatal rat cardiomyocytes. L-type Ca2+ channel α subunits coimmunoprecipitated with AMPKα. Atrial AMPK-activating phosphorylation was enhanced by 1 week of electrically maintained AF in dogs; fractional AMPK phosphorylation was increased in paroxysmal AF and reduced in longstanding persistent AF patients. - Conclusions - AMPK is activated by metabolic stress and AF, and helps maintain the intactness of atrial ICa,L, Ca2+ handling, and cell contractility. AMPK contributes to the atrial compensatory response to AF-related metabolic stress; AF-related metabolic responses may be an interesting new therapeutic target.